GERAKAN LITERASI SEKOLAH DI SEKOLAH DASAR NEGERI 1 KRANDEGAN BANJARNEGARA - Sodik, Bakhron (Penerbit CV Tentrem Karya Nusa, 2019)
This research is done to know (1) kinds of literacy, (2) strategy applied, (3) impact of applying of literacy movement in Krandegan Banjarnegara 1 Public Elementary School.. This reseach was conducted by using the type of qualitative approach descriptive research type. Data analysis is done through the stages of data colletion, data reduction, data presentation, and drawing conclusions. The results showed that: (1) the types of literacy contained in KrandeganBanjarnegara 1 Public Elementary School., among others, basic literacy, scientific literacy, library literacy, and technologi literacy. (2) a strategy applied by reading 15 minutes before learning begins, a reading corner in eacg class with students bringing books from home to school so that students can read whenever and wherever the literacy movement are integrated with the curriculum (curriculum 2013) write down the essense of reading or make a synopsis, discussion and presentatiton, the procurement of library materials. (3) the impact caused by the literacy movement such as the students showed the pencbant of writing, the increasing number of visits to the library, the creation of a literate enviroment with the habit of reading, easing burden ofteachers in training students ability to obtain information with high curiosity so that students have extensive knowledge and insight.Key Word: movement literacy, reading.